(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article shows the productive dialogue of scientific knowledge of the ХХI st century of technogenic civilization, the immanent value of which is technical-technological knowledge. The methodological advantages of their discovery are convergent NBICS- supertechnologies and information-communication technologies. The social significance of the subject and its productive force are the dominant of the post-industrial world, the system-forming principle and paradigmatic prerequisite knowledge determine the metaphysical understanding of complexity as a fundamental parameter of the ontological diversity of objective reality.